Tanggung Jawab Ahli Waris Notaris dan Perlindungan Hukum terhadap Penghadap atas Protokol Notaris yang Hilang atau Rusak - Bimo Lahkoro Anugroho (Universitas Negeri Medan, 2021)
This paper focuses on the topic of what is the responsibility of heirs who not submit notary protocols when the protocol is lost or damaged ?, What is the form of legal protection for notary clients or clients when the deed is lost or damaged? The method used in this paper is a normative juridical approach, using a statutory approach, conceptual approach, and case approach. The results of this paper indicate that the notary as public official who is in charge of making authentic deeds in his duties is also attached to the obligations to maintain the Notary Protocol. The Protocol shall be maintained and guarded properly by the Notary concerned or by the Notary Holder of the Protocol, and will remain in effect as long as or as long as the Notary's office is still required by the State. The form of the responsibility of a notary public or notary's heir for the notary's protocol when the deed is damaged or lost by negligence or deliberately related to the legal protection obtained by the applicant (client) for his deed at a later date. Then the notary concerned will be held accountable by making a report to the police for loss and damage, sending a report to the Minister of Law and Human Rights of the Republic of Indonesia regarding the condition of loss or damage then waiting for action to continue in the settlement process.